Assessment of State Services Quality and Availability in the Socio-Cultural Sphere - Terentyeva, Irina V.; Starodubtsev, Mikhail P.; Timonin, Andrey I.; Pugacheva, Natalya B.; Zykova, Nadezhda N.; Lunev, Alexander N.; Ezhov, Sergey G.; Starikova, Lyudmila D. (International Review of Management and Marketing, 2016)
The relevance of the presented research is caused by distribution of independent tools to assess public administration of the socio-cultural sphere by public nongovernmental organizations and scientific institutes. The objective of the paper is to develop a technique to assess quality and availability of state services in the socio-cultural sphere as components of public administration. An institutional approach has become a leading one; it allows to consider state services quality and availability assessment in the socio-cultural sphere as a complex indicator of the content quality of a resulting effect and quality of services obtained; it is also connected with the comfort of service rendering and their availability for consumers. The elaborated technique of state services quality and availability assessment in the socio-cultural sphere includes the following criteria: the level of state services quality; the level of state services availability; the level of trust that consumers have in service providers. The technique is directed to identify effective measures to provide consumers with available and high-quality state services in the socio-cultural sphere rendered by state bodies and their departments according to the results of a calendar year. Keywords: evaluation of public administration, trust of consumers in service providers, level of state services quality, level of state services availability, socio-cultural sphere. JEL Classifications: P35, Z13, Z18